Environmental awareness and occupational choices of adolescents - Patrick Lehnert [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2024)
„This paper analyzes the impact of environmental awareness on the occupational choices of adolescents. To do so, we exploit the apprenticeship system in Switzerland, where about two-thirds of adolescents choose an apprenticeship in their preferred occupation at around age 15. We consider two dimensions of environmental awareness as potential drivers of their occupational choice. First, we consider time-persistent regional social norms, which we proxy by regional differences in popular votes on environmental issues. Second, we investigate short-term shocks in environmental awareness, which we proxy by the occurrence of Fridays for Future strikes in different locations at different points in time. To measure whether adolescents choose occupations that have the potential to serve environmental protection, we estimate an occupational greenness score based on Swiss job-ad texts as data. Combining this occupational greenness score with detailed process-generated data on adolescents' applications from Yousty, Switzerland's largest online job board for apprenticeship positions, we find that environmental awareness is positively related to the greenness of adolescents' occupational choices. However, this finding applies only to short-term shocks in environmental awareness and not to time-persistent pro-environmental norms. We interpret this result as evidence for a social-movement effect on norms and values that significantly alter adolescents' occupational choices.” (authors’ abstract; BIBB-Doku)
Keywords: P 1.1 Jugendliche; L 5 Beratung & Orientierung; 370; Jugendlicher; Berufswahl; Berufswahlverhalten; Einflussfaktor; Umweltbewusstsein; Schweiz